Dating Violence Victimization, Nonsuicidal Self-Injury, and the Moderating Effect of Borderline Personality Disorder Features in Adolescent Inpatients. (August 2020) - Hatkevich, Claire; Mellick, William; Reuter, Tyson; Temple, Jeff R.; Sharp, Carla
The aim of the study was to examine whether Borderline Personality Disorder (BPD) features moderate the relation between dating violence victimization (DVV) experiences and nonsuicidal self-injury (NSSI) in adolescent inpatients. A total of 184 adolescent inpatients completed measures on DVV, BPD features, and NSSI at admission to treatment. Bivariate analyses revealed significant relations between DVV, BPD features, and NSSI. Hierarchical multiple regression analyses demonstrated a moderating effect of BPD features such that in the low BPD features group, more severe DVV was associated with greater NSSI frequency; adolescents in the high BPD group endorsed elevated, though stable, levels of NSSI at all levels of DVV. BPD features differentially affect the relationship between DVV and NSSI. Low BPD adolescents exposed to high DVV appear to self-injure more frequently and at rates similar to high BPD adolescents when faced with more severe DVV, while DVV appears neither necessary nor sufficient to be the cause of NSSI in high BPD adolescents. Our results indicate that DVV may be a particularly important focal point for treating adolescents who self-injure and have been victimized by a dating partner. As such, Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) and Dialectical Behavior Therapy (DBT) may serve as valuable clinical interventions.